The different scenarios of urgent carotid revascularization for crescendo and single transient ischemic attack. (February 2019) - Pini, Rodolfo; Faggioli, Gianluca; Gargiulo, Mauro; Gallitto, Enrico; Cacioppa, Laura M; Vacirca, Andrea; Pisano, Emilio; Pilato, Alessandro; Stella, Andrea
Objective: Carotid stenosis with crescendo-transient-ischemic-attack (cTIA) requires a prompt intervention to reduce the stroke risk. Few data are reported in literature about cTIA suggesting a different perioperative risk compared with patients with single TIA (sTIA). This study aimed to compare the outcome of carotid endarterectomy (CEA) in patients with TIA (single/crescendo) and evaluate the outcome risk-factors. Methods: Data from two tertiary hospitals for vascular treatment were analyzed from 2007 to 2016. All patients with TIA subjected to CEA were considered, comparing the 30-day postoperative stroke and stroke/death in patients with cTIA and sTIA, particularly in the urgent (≤48 h) setting. Results: On a total of 3866 CEA, 888 (23%) were performed in symptomatic patients and 515 for TIA: 365 (71%) patients with sTIA and 150 (29%) with cTIA. When compared with sTIA, cTIA patients were younger and less frequently affected by coronary disease, dyslipidemia, and chronic pulmonary disease; however, contralateral carotid occlusion was more common (20% vs. 10%, P  = .004; 56% vs. 46, P  = .03; 16% vs. 7%, P  = .01; >80 years 26% vs. 16%, P  = .01 and 2% vs. 10%, P  = .001; respectively). Postoperative stroke and stroke/death were significantly higher in cTIA compared with sTIA (5.3% vs. 1.6%, P  = .02 and 6.0% vs. 2.2%, P  = .03; respectively). Urgent CEA was performed in 58% ( n : 87) cTIA and in 11% ( n : 56) sTIA( P <.01). The urgent setting did not influence the stroke and stroke/death rate of CEA for sTIA (3.6% vs. 1.3%, P  = .21 and 3.6% vs. 1.9%, P  = .44, respectively), but was associated with lower rate of events in cTIA (1.1%vs. 11.1%, P  = .01 and 2.3% vs. 11.1%, P  = .03, respectively). This beneficial effect in patients with cTIA treated within 48-h was confirmed also by multivariate analysis (OR: 0.09, 95% CI: 0.76–0.01, P= .02). Conclusions: cTIA subjected to CEA have a higher stroke and stroke/death risk compared with patients with sTIA. The urgent setting seems to reduce the stroke/death rate cTIA; for sTIA with a stable neurological condition, the timing of CEA did not influence the outcome.